The excavation (Scottish Historical and Archaeological Internet Reports, 2012)
Detailed archaeological description of the results including the excavation of parts of the ditch and possible palisade around the manor. Six phases of activity have been identified. Phase 1 is probable limited prehistoric activity represented by a small number of artefacts and ardmarks although these could be related to medieval clearance of the site. In phase 2 a slot and a number of truncated post-pits preceded the stone buildings and cistern in phase 3. In phase 4 a concentration of four hearths or ovens were built inside one of the buildings. One of the buildings was used as a midden in phase 5 and this was followed by demolition and decay in phase 6.